Perancangan Jaringan VoIP Berbasis SIP pada Wireless Mesh Network (WMN) menggunakan Routing Protocol OLSR - Muhammad Afian Musthofa; Primantara Hari Trisnawan; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Voice over Internet Protocol (VoIP) is a technology which allow a long distance communication and conversation through a computer network. However the quality of VoIP technology performance is very dependent on the computer network used as a conducting media to fasilitate long distance communication and conversation especially in a place which had a heavy terrain. Therefore to achive the best performance of VoIP, it requires a computer network technology to support its maximum performance. One of the computer network technology which becomes a mainstay and could be use for VoIP is a Wireless Mesh Network (WMN) which has various advantages over conventional computer network. On this research, a WMN is composed of 5 Laptops as main Nodes and some other are for user as a foundation to build the VoIP Network. A VoIP network built above WMN would be supported by Session Initiation Protocol (SIP) Server which is also be built on one of the Node with Linux platform. To discover the quality and performance of the VoIP network, a test sequence is required as well as the analysis to determine the Quality of Service (QoS) by using Delay, Packet Loss, and Jitter as parameter. The result of this research, which consider the outcome of the Delay, Packet Loss, and Jitter paramater showed a result which can be categorized as ‘satisfying' and suitable for implementation.